Blood pressure assessment in children and adolescentes - Gabriel Dias Coêlho, Pedro; Maria Siqueira Neiva, Ana; de Sá Oliveira Lima, Gustavo; Antonio do Nascimento, Marcos (Seven Editora, 2023)
The elevation of blood pressure in childhood and adolescence has proven to be a worldwide public health problem, and its early identification and adequate treatment can contribute to a better quality of life in adulthood, avoiding the involvement of other chronic diseases resulting from poorly controlled arterial hypertension (AH), such as cardiovascular diseases and kidney problems. The stratification and identification of AH can help the public authorities to create public policies that are appropriate for children and teenagers. This chapter aims to discuss the theme of blood pressure assessment in children and adolescents, approaching current aspects in Brazil and worldwide. DOI: https://doi.org/10.56238/colleinternhealthscienv1-026